Development and validation of the respite care model for adults with cancer in Iran: study protocol for a multimethod research project - Vahid Pakpour; Fatemeh Sadeghi-Ghyassi; Azad Rahmani; Nasrin Kheibar; Maryam Rassouli (BMJ Open)
Introduction The primary caregivers of patients with cancer, especially in advanced stages, experience significant physical and emotional strain and require comprehensive support. Respite care has been acknowledged as an effective strategy to aid primary caregivers, and different models have been established in Western nations. However, implementing these models poses challenges due to notable cultural, social and healthcare system variances between Western and non-Western regions like Iran and other Middle Eastern countries. It is crucial to develop a model tailored to the country’s specific needs, culture and resources to systematically support caregivers and ensure care continuity. Hence, this study aims to develop and validate a respite care model for adult patients with cancer in Iran.Methods and analysis This study will use a multimethod approach across three stages. In the first phase, a scoping review will be conducted to identify, describe, conceptualise and implement the respite care system based on available documents and evidence. Then, a directed content analysis will be carried out to clarify care requirements and system establishment needs from stakeholders’ perspectives. Data from the scoping review and directed content analysis will be integrated to identify the crucial components of the model using the Delphi method in the second phase. In the third phase, another Delphi study will be conducted to assess the importance, scientific credibility and feasibility of the model, with the aim of finalising it.Ethics and dissemination This research project has received the code of ethics (IR.TBZMED.REC.1402.720) from Ethics Committee of Tabriz University of Medical Sciences. The findings of this study will be published in reputable journals and disseminated in accessible formats through various media channels.